Comparative phylogenetic analysis of CBL reveals the gene family evolution and functional divergence in Saccharum spontaneum - Feng, Xiaomin; Wang, Yongjun; Zhang, Nannan; Gao, Shuai; Wu, Jiayun; Liu, Rui; Huang, Yonghong; Zhang, Jisen; Qi, Yongwen (BMC plant biology, 2021)
The identification and functional analysis of genes that improve tolerance to low potassium stress in S. spontaneum is crucial for breeding sugarcane cultivars with efficient potassium utilization. Calcineurin B-like (CBL) protein is a calcium sensor that interacts with specific CBL-interacting protein kinases (CIPKs) upon plants' exposure to various abiotic stresses. In this study, nine CBL genes were identified from S. spontaneum. Phylogenetic analysis of 113 CBLs from 13 representative plants showed gene expansion and strong purifying selection in the CBL family. Analysis of CBL expression patterns revealed that SsCBL01 was the most commonly expressed gene in various tissues at different developmental stages. Expression analysis of SsCBLs under low K.sup.+ stress indicated that potassium deficiency moderately altered the transcription of SsCBLs. Subcellular localization showed that SsCBL01 is a plasma membrane protein and heterologous expression in yeast suggested that, while SsCBL01 alone could not absorb K.sup.+, it positively regulated K.sup.+ absorption mediated by the potassium transporter SsHAK1. This study provided insights into the evolution of the CBL gene family and preliminarily demonstrated that the plasma membrane protein SsCBL01 was involved in the response to low K.sup.+ stress in S. spontaneum.